Author Correction: Rapid Fabrication of Reinforced and Cell-Laden Vascular Grafts Structurally Inspired by Human Coronary Arteries (Nature Communications, 2019 10 1 3098 10.1038/S41467-019-11090-3) - Garcia-Herrera, C (Nature Publishing Group, 2019)
The original version of this Article contained an error in the spelling of the author Jekaterina Maksimcuka, which was incorrectly given as Jekaterina Maksimuck. This has now been corrected in both the PDF and HTML versions of the Article. Additionally, the original PDF version of this Article contained an error in Figure 6c in which a third stress-strain curve was erroneously shown. The correct version of Fig. 6c is: (Figure presented.). © 2019, The Author(s).